2015
DOI: 10.7314/apjcp.2015.16.2.401
|View full text |Cite
|
Sign up to set email alerts
|

Early Diagnosis Behavior in Turkish Women with and without a Family History of Cervical Cancer

Abstract: Background: This study was planned as comparative and descriptive in order to measure and evaluate the knowledge and attitudes regarding early diagnosis of women with and without a family history of cervical cancer. Materials and Methods: The study sample consisted of the relatives of female patients (N=253) who were admitted to Istanbul University of Medicine. Women with a family history of cervical cancer formed the case group, while those without family history of cervical cancer constituted the control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
2
1
Order By: Relevance
“…In our study, the healthy lifestyle behaviors of students with a cancer patient among family or relatives were on a better level compared to those without. In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32).…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 52%
“…In our study, the healthy lifestyle behaviors of students with a cancer patient among family or relatives were on a better level compared to those without. In other studies, status regarding having a cancer patient among family or relatives was found to affect early diagnosis behavior positively, increase knowledge on cancer, and provide improvement in healthy lifestyle behavior (26)(27)(28). Contrary our study, some studies in literature have found that status regarding having a cancer patient among family or relatives doesn't affect behavior regarding protection from cancer (20,(29)(30)(31)(32).…”
Section: Does Familial History Of Cancer Affect the General Health Cocontrasting
confidence: 52%
“…Using the HBM framework, this study found that women's beliefs in the preventive measure of Pap smears were an important factor in influencing their decisions to go for it. Knowledge of the benefits of Pap smears was found to be significantly associated with Pap smear uptake in previous studies (Gu et al., ; Gunaydin & Gencturk, ; Lee, Fogg, & Menon, ; Roy & Tang, ). Although this study did not directly measure the association between knowledge and belief in the effectiveness of Pap smears, 56% of the participants were able to correctly identify the purpose of a Pap smear test.…”
Section: Discussionmentioning
confidence: 74%
“…Its validity and reliability study for Turkey was performed. Of the scale, Cronbach's alpha= 0.6667 and standardized item alpha= 0.6545 [9].…”
Section: Data Collection Toolsmentioning
confidence: 99%